Pengaruh Quality Of Work Life Dan Lingkungan Kerja Terhadap Kepuasan Kerja Karyawan Di Dinas SosialKota Malang - Imam Rohedi; Andi Nu Graha; Sri Wilujeng (Jurnal Riset Mahasiswa Manajemen, 2018)
Job satisfaction is a person's emotional response to work situations and conditions. This study aims to determine 1) The effect of quality of work life and work environment on employee job satisfaction, 2) The effect of quality of work life on employee job satisfaction, 3) The effect of work environment on employee job satisfaction. This research was conducted at the Social Service of Malng City. This type of research is quantitative research. The population and sample of this study were 30 civil servants. Methods of data collection using questionnaires, interview observation, and documentation. The results showed that the quality of work life and work environment had a positive and significant effect on employee job satisfaction in the Social Service of Malng City. The better the quality of work life and work environment, the better job satisfaction of employees.